Increasing Work Efficiency with Negative Reinforcement - ทองบุญตา ธันยนันท์ (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
To work with many people with different background and work habits. How the administrators handle with them to help the organization reach the effectiveness and achieve the goal. One interesting way is behavior modification for employees using reinforcement. However, the more important thing is the administrators have to understand individual differences. All the individuals differ from each other in attitude, need and learning habits. Hence, the administrators should consider and choose the suitable reinforcement techniques to motivate employees’ desired behaviors. In some situations it might not be successful to use positive reinforcement. Then negative reinforcement techniques might be another ways to be implemented for maintaining the discipline and increasing work efficiency within organization for example, ordering, setting the rules and regulations and reprimanding etc.